Biomechanical Modeling and Evaluation of Buttocks Automatic Assisted Repositioning in Bedridden Patients - Liqing Yang; Ganjun Song; Di Luo; Haotian Xu; Jiamei Han; Mingzhao Xiao; Dingqun Bai; Shan Tian; Wensheng Hou; Jisi Tang; Xin Zhang; Lin Chen (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Pressure ulcers (PUs) pose a significant challenge in the care of bedridden patients, to which automated tilt nursing beds have emerged as a promising solution. However, the lack of effective models to elucidate the mechanical responses of deep tissue during assisted repositioning and identify the optimal tilt angle has hindered the implementation of effective automatic assisted repositioning systems for long-term care patients. Therefore, this study developed a novel computational model that integrates the buttocks with a support mattress to simulate automatic assisted repositioning, thereby analyzing deep tissue responses and optimizing tilt angles for effective load offloading. Inverse modeling was used to reconstruct the 3D shape of the buttocks, nodal equivalence techniques were employed to simplify the mesh and accurately represent internal tissue contacts, and soft tissue parameters were optimized using Response Surface Methodology (RSM). Finally, finite element (FE) analysis was conducted to evaluate the biomechanical responses and optimize the repositioning strategies. Model validation demonstrated a deformation error of $6.93~± ~7.41$ mm (mean ± standard deviation) and interface pressure differences within 22.4%, demonstrating the efficacy and bio-fidelity of the system. Repositioning simulations at angles from 0° to 30° showed a 20% reduction in total soft tissue strain, with peak equivalent stress decreasing by 22.27% at the mattress- to-buttock interface and by 20.43% at the muscle-to-adipose tissue interface. These simulations suggest that a 30° turning angle is beneficial for alleviating pressure concentration, which may inspire the design and optimization of automatic assisted repositioning strategies in rehabilitation practices.